Characterization of VC Coatings on Cold Work Tool Steel Produced by TRD - Elhelaly, M.A.; El-Zomor, M.A.; Youssef, A.O.; Attia, M.S. (Manufacturing Technology Journal, 2021)
In This study vanadium carbide coatings obtained by thermo-reactive deposition/diffusion (TRD) technique on cold work tool steel AISI D3. The TRD treatment were carried out in a molten mixture consisting of NaCl, CaCl2, ferrovanadium and aluminum, by heating this mixture at 1000 °C for 4h using a resistance-heating furnace under air atmosphere. The coating process was investigated using light microscopy LM, scanning electron microscopy/energy dispersive spectroscopy SEM/EDS, and X-ray diffraction XRD characterization techniques. The results indicated that the vanadizing process produced a homogeneous coating layer about 13 µm depth and its microhardness is 2300 HV. Carbide compounds that are formed are vanadium carbides phases (V8C7, VC, V4C3, V6C5, V2C), while EDS-Line scan results show chromium carbides phases formed in sublayer. The corrosion resistance of the vanadium carbide coatings was evaluated using potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) in a solution of 3.5 % NaCl. Vanadium carbide coatings improved the corrosion resistance of the substrates, vanadium carbide coatings showed the longest service life compared with the uncoated tool steel AISI D3.
Keywords: Thermo-Reactive Diffusion; Vanadium Carbide Coating; Microhardness; Corrosion; Tool Steel